2023
DOI: 10.1101/2023.06.23.546355
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Uncovering a stability signature of brain dynamics associated with meditation experience using massive time-series feature extraction

Abstract: Previous research has examined resting electroencephalographic (EEG) data to explore brain activity related to meditation. However, this research has mostly examined power in different frequency bands. Here we compared >7000 time-series features of the EEG signal to comprehensively characterize brain activity differences between meditators and non-meditators. Eyes-closed resting-state EEG data from 49 meditators and 46 non-meditators was decomposed into the top eight principal components (PCs). We extracted… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 107 publications
0
0
0
Order By: Relevance
“…Furthermore, the study using EEG and modelling showed that the enhanced thalamocortical functional connectivity was associated with increased dynamic stability of the EEG activity (Saggar et al, 2015). Applying a comprehensive data-driven approach to analyse the resting EEG data reported in the current study, we also found that meditators had higher dynamic stability of their EEG activity compared to the non-meditators (Bailey et al, 2024).…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Furthermore, the study using EEG and modelling showed that the enhanced thalamocortical functional connectivity was associated with increased dynamic stability of the EEG activity (Saggar et al, 2015). Applying a comprehensive data-driven approach to analyse the resting EEG data reported in the current study, we also found that meditators had higher dynamic stability of their EEG activity compared to the non-meditators (Bailey et al, 2024).…”
Section: Discussionsupporting
confidence: 60%
“…The first study included a total of 34 experienced meditators and 36 healthy control non-meditators, and the second study included a total of 39 meditators and 36 healthy control non-meditators. Both studies included the recording of eyes-closed resting EEG data (Bailey et al, 2024; McQueen et al, 2023) and a Go/No-go task that presented Go and No-go trials with equal probability, with no more than three of each trial type presented consecutively (Bailey, Freedman, et al, 2019; Bailey et al, 2023b; Bailey, Raj, et al, 2019). However, due to time constraints within the recording sessions, not all participants provided both types of recordings, and some recordings were excluded due to artifact contamination.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For studies that handselect a single feature of interest (like a metric of autocorrelation timescale) [4,5], the large range of alternative features are left untested, leaving open the possibility that alternative statistics could be more informative and interpretable. Applications that have systematically compared the performance across a large feature library, such as hctsa [3,8,17,6,18,19], have involved substantial computational expense and statistical care in dealing with high-dimensional feature spaces (often requiring correction across thousands of features, limiting the power to detect signals in smaller samples). fMRI time series are short, noisy, and-particularly in the restingstate regime where dynamics may be approximated as close to a steady-state-are generally well-suited to being characterized by linear time-series analysis methods [20,21].…”
Section: Introductionmentioning
confidence: 99%